Fuzzy Almost Nearly Prime and Fuzzy Almost Nearly 2 Absorbing Submodules - O. Kadem, Khudhayer (Al-Nahrain Journal of Science, 2024)
We present in this work the concepts of fuzzy AlmostNearlyprime submodules and fuzzy AlmostNearly2Absorbiing submodules as popularizations of fuzzy Nearly prime submodules and fuzzy 2-Absorbing submodules. Numerous additional fundamental characteristics, attributes, and connections between these ideas and other ideas are provided.